No proxy for quality: why journal rankings in political science are problematic for political theory research. Issue 3 (3rd July 2019) - Bankovsky, Miriam
ABSTRACT: Journal rankings for political science have been regularly published, from the 1970s onwards, by the American Political Science Association's 'state of the discipline' journal. Politics journals have also been officially ranked by the Australian Political Studies Association into four bands (A*, A, B and C) from 2007 onwards. This article shows, first, that the assumption grounding these exercises (namely, that disciplinary journal rankings can serve as proxies for the quality of articles in their pages) is undermined by the findings of the broader research evaluation literature, especially with respect to sub-disciplines (like political theory, Australian politics, and some types of qualitative comparative politics) that bear certain characteristics. Next, outlining the findings of a 2018 survey, it is argued that the disciplinary use of journal rankings in political studies not only has damaging effects on research in political theory, but also advantages other sub-disciplines. The paper closes with two recommendations.